1984
DOI: 10.1164/arrd.1984.129.5.798
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Adherence in Pulmonary and Systemic Arterial Blood Samples from Patients with Adult Respiratory Distress Syndrome1–4

Abstract: The accumulation of granulocytes in lung capillaries, caused by increased granulocyte adherence in response to circulating inflammatory mediators, is proposed as one mechanism of pulmonary vascular injury in the adult respiratory distress syndrome (ARDS). The adherence characteristics of granulocytes from humans with this syndrome have, however, not been described. We assayed the granulocyte adherence to nylon fiber columns using whole blood samples collected from the pulmonary artery of 14 patients within 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…The observations are important because the mechanisms by which chemotactic factors and humoral inflammatory mediators promote PMN adherence to endothelium are not clearly defined. Although under some conditions chemotactic factors such as fMLP, LTB4, and C5a fragments may enhance neutrophil adherence by acting on the endothelium (48)(49)(50), each of these mediators also directly stimulates the adhesiveness of the neutrophils (20,24,25,48,49,51). A recent report suggests that a direct action on the neutrophils is the dominant effect of C5a, C5a desarg, and fMLP (51).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The observations are important because the mechanisms by which chemotactic factors and humoral inflammatory mediators promote PMN adherence to endothelium are not clearly defined. Although under some conditions chemotactic factors such as fMLP, LTB4, and C5a fragments may enhance neutrophil adherence by acting on the endothelium (48)(49)(50), each of these mediators also directly stimulates the adhesiveness of the neutrophils (20,24,25,48,49,51). A recent report suggests that a direct action on the neutrophils is the dominant effect of C5a, C5a desarg, and fMLP (51).…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophils were isolated from venous blood using dextran sedimentation and Ficoll-Hypaque gradients as described (20). A group of healthy subjects of various ages and both sexes served as PMN donors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moore, Silliman, and others (52)(53)(54) have shown that PAF is a primary agent responsible for neutrophil priming in human trauma victims. In contrast, LPS and TNF␣ are the likely priming agents in acute pancreatitis (55,56), as well as in many patients with sepsis (57)(58)(59)(60)(61), and these agents have been directly implicated in causing acute lung injury (62)(63)(64)(65) and ischemia-induced acute renal failure (66).…”
mentioning
confidence: 99%